Juvenile justice: between State protectionism and the guarantee of rights - Hurtado Rodríguez, Hernando (Cuadernos de Trabajo Social, 2013)
Is juvenile justice a problem of juridical visions or of social realities? This is a very important query to the degree that it has guided the current debate on juvenile justice in a large number of Western societies. The problems that juvenile justice raises are crisscrossed by different juridical or social concepts that seek to address the topic of youthful offenders of the law. Consequently, what is presented here is a theoretical description of the two fundamental aspects that have guided the operation of the juvenile penal justice from the middle of the nineteenth century and throughout the twentieth century. Then, a third section of this article is a presentation of some aspects of the social reality experienced by a large part of adolescent offenders in the Colombian context, as a means of presenting some possible points of discussion and reflection useful for a holistic perspective of professional intervention of Social Work.
Keywords: adolescent offenders; juvenile delinquency; juvenile penal justice; paradigm of integral protection; guardian paradigm.